Electron diffraction data for some members of the metatorbernite group - Jiménez de Abeledo, María E.; Rodríguez de Benyacar, María A.; Galloni, Ernesto E. (The American Mineralogist Society of America, 1968)
Fil: Jiménez de Abeledo, María E. Comisión Nacional de Energía Atómica; Argentina